Recovery from fatigue of pneumatic artificial muscle using a thermoplastic elastomer. (1st December 2020) - Tomori, Hiroki; Sasama, Takuma; Ando, Shingo
Abstract : Robots, driven by soft actuators, aim at ensuring human safety. Owing to their relatively higher output force than other soft actuators, rubber pneumatic artificial muscles (PAM) are actively researched. In particular, straight-fiber pneumatic artificial muscle (SFPAM) has high output and contraction abilities. However, significant deformation places substantial strain on rubber, shortening the lifespan of artificial muscle. Therefore, improving the lifespan of artificial muscle is important for practical applications. To achieve this, this study proposes the use of a repairable elastomer with artificial muscle. We suggest that the lifespan of artificial muscle can be improved using a maintenance process. Herein, styrene-ethylene-propylene-styrene (SEPS), a type of thermoplastic elastomer, was selected and a heat-based maintenance method proposed. Fatigue test results using the SEPS sample showed an increase in fatigue lifespan using the proposed heat treatment. However, we also have to address undesired deformation of SEPS exhibiting plastic property by heating. To avoid contact with SEPS during heating, we proposed contactless heating method with microwave. To make SEPS catch microwave, we created carbon black-blended SEPS samples. Fatigue tests indicated that the heat treatment method with microwave also increased the lifespan of carbon black-blended SEPS samples. GRAPHICAL ABSTRACT: UF0001